The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1108/bfj-02-2017-0092
|View full text |Cite
|
Sign up to set email alerts
|

Internal resources as tools to increase the global competition: the Italian wine industry case

Abstract: Purpose The purpose of this paper is twofold: first, it identifies distinct organizational models in a sample of small and medium enterprises operating in the Sicilian wine industry; and second, it identifies the key factors enabling a superior export success. Design/methodology/approach Internal resources were analyzed theoretically in order to achieve the aims of the study. Subsequently the empirical investigation was carried out administering a questionnaire to a sample of 102 wineries in Sicily, Italy. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 51 publications
5
49
1
2
Order By: Relevance
“…Several studies on operation and strategic management use the RBV theory,because it is an effective approach to explain the way in which internal resources can be combined to generate a sustainable competitive advantage (Shams, 2016a;Galati et al, 2017),which is different from thevision that the external market forces and the positioning of the same company in the market exert a relevant influence on the possibility to create a competitive advantage (Porter, 1985). The RBV theory is based on both traditional assumptions adopted in other strategic management theories, such as that firms are profit-maximizing entities and that managers in firms are rational, and introduce two additional assumptions: resource heterogeneity, that incorporate two attributes of firms' resources, which are linked to the scarcity and nonsubstitutability, and resource immobility (Barney, 1991).…”
Section: Resource Based View and The Randd Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on operation and strategic management use the RBV theory,because it is an effective approach to explain the way in which internal resources can be combined to generate a sustainable competitive advantage (Shams, 2016a;Galati et al, 2017),which is different from thevision that the external market forces and the positioning of the same company in the market exert a relevant influence on the possibility to create a competitive advantage (Porter, 1985). The RBV theory is based on both traditional assumptions adopted in other strategic management theories, such as that firms are profit-maximizing entities and that managers in firms are rational, and introduce two additional assumptions: resource heterogeneity, that incorporate two attributes of firms' resources, which are linked to the scarcity and nonsubstitutability, and resource immobility (Barney, 1991).…”
Section: Resource Based View and The Randd Domainmentioning
confidence: 99%
“…In particular, if tangibleresourcesare often easier to imitate, the intangible resources, linked to the human capital within the company and their competences or based on the company reputation in the market, are often more difficult to imitate, andthus, be able tocontribute to an effective and sustained competitive advantage.For these reasons, scholars agree that human resources (the collective knowledge, skills and abilities) as the intangible asset and the brand as a quite similar intangible asset constitute the most important resources available to firms (Scuotto et al, 2017;Del Giudice et al, 2015;Capitello et al, 2014;Stokes &Oiry, 2012). Irrespective to the category in which the resources fall they are organized and coordinated by firms so that they enable the firm to plan and implement efficient strategy that results in gaining a competitive edge (Del Giudice&Straub, 2011; Galati et al, 2017). A finding from the wine industry plays a crucial role, as De Salvo et al (2017) put in evidence in exploring how human capital affects wineries' performances, to this end suggesting political measures to wider invest in this area.…”
Section: Resource Based View and The Randd Domainmentioning
confidence: 99%
“…In the studies of Festa et al (2015) and Galati et al (2014) it was analyzed wine/territory, as a key driver in the wine marketing and found the link between locality and wineries and business success. Many other studies (Fernandez Olmos, 2011; Galati et al, 2017b) found that a company's level of investment in wines advertising influence on company's performance.…”
Section: Literature Reviewmentioning
confidence: 96%
“…el modelo anterior a la globalización actual del mundo del vino lasáreas de enología y viticultura eran las dominantes, en la situación actual la economía y el marketing ocupan un lugar tan destacado como ellas. La necesidad de profesionalización abarca a todas las actividades [10][11][12], ya que no es posible exportar sin segmentar los mercados y sin establecer redes más complejas de coordinación vertical entre los actores de la cadena, lo que a menudo supone un aumento de las operaciones intra-industriales [13]. Todo esto exige a las empresas vitivinícolas mayores recursos en lasáreas de gestión, comercialización, distribución y marketing [14], y un gran esfuerzo para avanzar rápido en la curva de aprendizaje de los mercados internacionales [15].…”
Section: Introductionunclassified